Circumflex arterial sulcus of the scapula (sulcus arteriae circumflexae scapulae): its anatomy and clinical relevance - Strnad, Tomáš; Bartoníček, Jan; Tuček, Michal; Naňka, Ondřej (Surgical and radiologic anatomy, 2022)
INTRODUCTION: The circumflex scapular artery (CSA) has been described in detail in the literature, but the groove, i.e., the circumflex sulcus (CFS), formed by the artery on the lateral pillar of the scapula has been completely neglected. The aim of the present study was to describe the variability and anatomy of the CFS. MATERIALS AND METHODS: The study was based on the examination of 103 pairs of dry bone specimens of adult scapulae, i.e., 206 specimens, including 92 (46 pairs) male and 114 (57 pairs) female specimens. In the first step, quantitative criteria were defined for assessment of the CFS presence and type. Subsequently, statistical analysis of the obtained data was performed. RESULTS: The study revealed considerable variability of the arterial groove, which was well developed in 33% (type A), shallow in 40% (type B), and absent in 27% (type C) of cases. The mean distance between CFS and the infraglenoid tubercle was 3.3 cm CI0.95 (3.1-3.3), which corresponds to the proximal third of the lateral border of the scapula. CONCLUSION: The study has confirmed variability of the arterial groove (CFS) and its localization in relation to the inferior glenoid rim. The findings are clinically important, particularly in relation to the Judet approach to scapular fractures (localization of the CSA course).
Keywords: dospělí; syndrom chronické únavy; lidé; Female; Scapula; mužské pohlaví; Arteries; Male; Fatigue Syndrome, Chronic; arterie; Adult; lopatka; ženské pohlaví; Humans